Experimental study on compressive behavior of PE-ECC under impact load - Liu, Lingfei; Xiao, Jie; Wu, Zijian (Frontiers in Materials, 2023)
Compared with polyvinyl alcohol-engineered cementitious composites (PVA-ECC), engineered cementitious composites containing polyethylene fibers (PE-ECC) has captured the attention of researchers because of lower cost. Nevertheless, there is a limited amount of research that focuses on their dynamic behavior. Thus, specimens with different water binder ratios were tested by split Hopkinson pressure bar (SHPB) to unveil the dynamic compressive behavior of PE-ECC. The dynamic behaviors were analyzed based on the tests, including dynamic failure modes, dynamic stress-strain curves, dynamic compressive strength, dynamic peak strain, and dynamic toughness. The result shows the PE-ECC has excellent compressive ductility, and a long post-peak descending part in the stress-strain relations. Furthermore, the sensitivity analysis reveals that the strain rate is the most crucial factor that directly affects the dynamic compressive strength, dynamic peak strain, and dynamic toughness in a monotonic fashion.